Analisis Spasial Evaluasi Kesesuaian Lahan Tanaman Hortikultura pada Lahan Pertanian di Kecamatan Sidemen, Kabupaten Karangasem - Sinaga, Irene Levina Yulianti; Mega, I Made; Trigunasih, Ni Made (Nandur; Vol 3 No 4 (2023), 2023)
Horticultural crops, especially fruits and vegetables contain nutritional components, namely sources of vitamins and minerals needed to support human nutritional needs. To produce horticultural crops optimally, it is necessary to evaluate land suitability. This study aims to determine actual and potential land suitability classes as well as spatial distribution for horticultural crops, limiting factors, and land use directions that can be recommended on dry land in Sidemen District. This research was conducted using survey methods, soil analysis in the laboratory, and land suitability classification using the 2011 Ritung land evaluation technical guidelines by matching the quality/characteristics of the land with the growing requirements of the plants being evaluated. The horticultural crops evaluated included Chinese cabbage, red chilies and long beans. The results showed that the actual land suitability class for horticultural crops (petsai, red chili, and long beans) was classified as S3 (marginally appropriate) up to N (not suitable) with the limiting factors of temperature, rainfall, texture, P-available, and slope. Potential land suitability classes for horticultural crops (petsai, red chili and long beans) are classified as S1 (very suitable) to S3 (marginally suitable) with the limiting factors of temperature, texture and slope. Efforts to improve land suitability class can be done by cropping pattern setting, applying fertilizers, and making terraces.